(untitled) (International journal of artificial intelligence, 2026)
This article provides a scientific and methodological analysis of the role and effectiveness of 0-based learning technologies in developing creativity among primary school students during natural science lessons. The processes of creating problem situations, asking inquiry-oriented questions, drawing conclusions based on experiments and observations, and conducting analysis are considered key factors in developing students’ creative thinking, independent decision-making, and problem-solving skills. The research results indicate that purposeful use of problem-based learning technologies significantly increases the level of creativity among primary school students.